Extraction of phenolic compounds and flavonoids compounds from Orthosiphon Stamineus - Zhu, Lau Mei (2013)
Phenolic and flavonoids compounds present in Orthosiphon stamineus (OS) exhibit high antioxidant capacity. This research was conducted to compare ultrasonic-assisted extraction (UAE) and microwave-assisted extraction (MAE) with maceration and investigate effects of solvents (70%-30% v/v methanol-water, 70%-30% v/v propanol-water, 50%-50% v/v methanol-water, 50%-50% v/v propanol-water, water, methanol and propanol), extraction time, microwave power and extraction temperature on Rosmarinic acid and Sinensetin extraction yields from OS dried powder. The extraction yields were analyzed by using Ultra Performance Liquid Chromatography (UPLC) and were compared to standard calibration curve with their retention times. Results from Total Phenolic Content (TPC) were used to support UPLC result. By UAE, the highest yield for Rosmarinic acid could be obtained with following conditions: 70%-30% v/v Methanol-water as solvent with extraction time of 90 minutes at 60 ̊C. The highest yield for Rosmarinic acid that could be obtained by using MAE was with following conditions: 70%-30% v/v Methanol-water with extraction time of 120 s at 450 W. By UAE, the highest yield for Sinensetin could be obtained with following conditions: propanol as solvent with extraction time of 90 minutes at 60 ̊C. Meanwhile, the highest yield for Rosmarinic acid that could be obtained by using MAE was with following conditions, 70%-30% v/v Methanol-water with extraction time of 120 s at 450 W. UAE and MAE can replace maceration in extraction of phenolic compounds and flavonoids compounds since UAE and MAE had higher yields than maceration in shorter time. Recommendations suggested in order to obtain optimization of this research were to study more effects or parameters in both UAE and MAE.